Hygiene and Sanitation Condition in the Karangayu Market Regional Technical Implementation Unit - Pamungkas, Pradico Dwi (Journal of Public Health for Tropical and Coastal Region, 2023)
Background: Lack of access to sanitation and hygiene in the traditional market can increase infectious disease transmission. Based on a preliminary study in the Karangayu Market, it was found that the hygiene and sanitation condition did not meet the requirements of Minister of Health regulation No. 17 of 2020. The purpose of this study was to determine the condition of market hygiene and sanitation in the working area of Karangayu Market Regional Technical Implementation Unit, Semarang City, Central Java, Indonesia. Methods:  This observational study was conducted in all of the eight markets located in the working area of Karangayu Market Regional Technical Implementation Unit. A score of ≥ 70% of the total score of each variable was determined as met the requirement and the score of ≤ 70% was defined as did not meet the requirements. The determination of the scores was done through the observation using sanitary assessment, based on the Ministry of Health Regulation No. 17 of 2020. Results:  The condition of market hygiene and sanitation in the working area of Karangayu Market, Semarang City had not met the requirements. The used indicators were traders/employees, visitors, market buildings, garbage disposal sites, drainage ditches, toilets, places to sell food and groceries, control of disease-carrying animals, parking lots. However, the level of density of flies was still met the requirements. Conclusion: Poor hygiene and sanitation in the working area of Karangayu Market Regional Technical Implementation Unit, Semarang City, can increase the risk for disease transmission if it is not resolved.